2009
DOI: 10.1007/bf03326071
|View full text |Cite
|
Sign up to set email alerts
|

Chemical speciation of fine particle bound trace metals

Abstract: ABSTRACT:This study reported quantifications of fine particle bound trace metals and their potential health risks for residents in Guangzhou, a rapidly developing and most populated city in South China. The fine particle samples were collected from October 29 th. to November 8 th. of 2006 at two different elevations in a mainly residential area and analyzed for the total concentration of aluminum, iron, zinc, lead, manganese, copper, arsenic, chromium, nickel, cadmium, molybdenum and cobalt. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(66 citation statements)
references
References 29 publications
4
62
0
Order By: Relevance
“…The reason was that the speciation of metals was influenced not only by its geochemistry characteristics but also by the human activities and the physical and chemical features of the sediments (Feng et al 2009;Wang et al 2012).…”
Section: Speciation Of Heavy Metals and Metalloid In Sedimentsmentioning
confidence: 99%
“…The reason was that the speciation of metals was influenced not only by its geochemistry characteristics but also by the human activities and the physical and chemical features of the sediments (Feng et al 2009;Wang et al 2012).…”
Section: Speciation Of Heavy Metals and Metalloid In Sedimentsmentioning
confidence: 99%
“…It occurs in soil and minerals and it may enter air, water and land and uptake by plants (Mahzuz et al, 2009;Reza and Singh, 2010). Plants vary considerably in their tolerance of arsenic and in the amount of arsenic that they can take up from soils and water (Goyal et al, 2008;Feng et al, 2009;Malakootian et al, 2009;Urik et al, 2009). Arsenic is a naturally occurring element present in the both inorganic and organic forms in different environmental and biological samples and its concentrations may be increased by anthropogenic contamination (Villa-Lojo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Feng et al [95] found also that ca. 70% of the As was associated to the first and the second fractions for PM2.5 of Guangzhou (China).…”
Section: Sample Sequential Extraction For Total Asmentioning
confidence: 72%